Sedimentation - Maric, Filip; Poto, Margherita Paola; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To understand the role of sedimentation in creating the unique conditions of ocean floor ecosystems. Learning objectives: With this activity, pupils will gain a basic understanding of how sediments in the ocean settle on the ocean floor (sedimentation) and what this looks like. Key words: Settling, sediment, terrigenous, pelagic.